Data-Driven Learning Community Planning: The Principal’s Strategy in Teacher Professional Development - Tumiyati, Tumiyati; Nurkolis, Nurkolis; Ariyanto, Lilik (International Journal of Active Learning, 2025)
Improving the quality of basic education requires school leadership that can drive teacher professional development through a planned and data-driven learning community. This study aims to describe the principal's strategy in planning the Professional Learning Community (PLC) at SD Negeri Temperak, analyze data-based strategic steps in preparing teacher learning community programs, and identify supporting factors and obstacles that affect its implementation. The approach employed is qualitative, utilizing a case study design through data collection techniques that include in-depth interviews, observations, and document analysis. These data are then analyzed using thematic analysis methods. The results of the study show that school principals play a central role in utilizing education report card data to identify learning needs, formulate teacher development priorities, and develop PLC agendas collaboratively. Systematic and evidence-based planning has been proven to strengthen teachers' reflective practices, enhance learning effectiveness, and positively impact student learning outcomes, particularly in literacy and numeracy. The main obstacles identified include time constraints, dependence on school principals' leadership, and a lack of optimal continuous evaluation. These findings confirm the importance of adaptive, collaborative, and data-driven leadership in learning as a foundation for teacher professional development in elementary schools.